Effect of Antioxidant Capsule Supplementation on Oxidative Stress Markers in Hypertensive Patients - Novaes-Gaeta, Ludmila N; Moraes, Mariele C; Katayama, Keyla Y; Sangaletti, Carine T; Irigoyen, Maria Claudia; Freitas, Sarah; Viana, Ariane; De Angelis, Katia; Caldini, Elia G; Ferreira Lopes, Heno (Scripta Medica, 2024)
Background/Aim: Hypertension is a consequence of a neuromodulatory imbalance and is directly associated with cardiovascular diseases. Oxidative stress constitutes an intermediate pathophysiological mechanism for hypertension and cardiovascular disease. Evidence suggests that there is a proportional relationship between diets high in antioxidants and a reduced risk of cardiovascular events. A high antioxidant diet could scavenge the free radicals and other toxic radicals offering better protection to the cardiovascular system. The primary study objective was to evaluate the impact of dietary supplementation with fruit extract capsules on markers of oxidative stress and antioxidant capacity in hypertensive and normotensive individuals; a secondary objective was to evaluate the impact of dietary supplementation on insulin resistance, markers of inflammation and hemodynamic variables in treated hypertensive and normotensive patients. Methods: This clinical trial comprised 30 hypertensive patients and 29 normotensive volunteers. Study participants received placebo capsules for 4 weeks, then fruit extract capsules (blueberry, cranberry and pomegranate), one capsule of each per day for 4 weeks. Blood pressure was measured at baseline, after the use of placebo and antioxidant capsules. Catalase, thiobarbiturate acid reactive substances (TBARS), superoxide dismutase (SOD), carbonyl and ferric-reducing antioxidant powder (FRAP) were used to evaluate oxidative stress. Results: The mean age among hypertensive participants was 49.3 ± 9.3 years. Catalase increased in both groups; reduction of TBARs, FRAP and carbonyls occurred in the hypertensive group. A significant intragroup difference in homeostatic model assessment of insulin resistance (HOMAir) was noted between normotensive and hypertensive individuals at different times. No significant difference occurred regarding inflammatory cytokines, adipocytokines and haemodynamic data after antioxidant consumption. Conclusion: The study results suggest that supplementation with fruit capsules rich in antioxidants for 4 weeks significantly reduces oxidative stress in hypertensive patients. Studies with a larger number of patients are needed to confirm the findings.